The Description of Elderly Physical Activity during COVID-19 Pandemic in Nursing Home of Banyuwangi - Faiq Rojannah; Latifa Aini Susumaningrum; Tantut Susanto; Hanny Rasni; Fahruddin Kurdi (KHD-Production, 2022)
The elderly experience limitations in carrying out physical activities during the COVID-19 pandemic which can reduce the welfare of the elderly. Due to the aging process, physiological changes and decreased immune function in the elderly make the elderly group a group with a high risk of exposure to COVID-19. The purpose of this study was to describe the physical activity of the elderly in the Nursing Home of Banyuwangi. Descriptive quantitative research was performed among 32 elders in May 2021. A self-administered questionnaire was used to identify characteristics of the elderly and their physical activity with the Physical Activity Scale for Elderly (PASE). The One-sample Kolmogorov-Smirnov’s test was used to reach the goal of this study. The result shows that the physical activity of the elderly didn’t significantly change during the pandemic t = 0,119; p-value 0,200. It can be concluded that there is no significant change in elders’ physical activity during the COVID-19 pandemic.